The Language Faculty between Acquisition and Learning: A Critical Review - Abdeldaim, Erfan (IIUM Journal of Educational Studies, 2022)
Experts and practitioners in the field of teaching foreign languages see the difficulty experienced by the learner of the foreign language. These difficulties are different from one learner to another according to the difference in the learning environment and the motivation of the learner. On the opposite of that, the easy acquisition of the first language raises a serious issue that while the child acquires his mother language easily and smoothly, the foreign language learner faces many difficulties during the journey of learning the foreign language. This issue requires proper research, especially in the field of teaching Arabic to non-native speakers. This research attempts to employ the mechanisms of language acquisition in the learning processes considering the considerable experience of the researcher as a language educator in various educational institutes. Hence, this research seeks to identify the aspects of agreement and difference between language acquisition and learning and employ language acquisition strategies in language teaching classes. The researcher explores the literature related to these two processes, then analyzes the aspects of the agreement, disagreement, motivation, reasons, methods, and strategies. He examines how to transform the foreign language class from the process of language learning to the process of language acquisition. There is no doubt that this depends on the teacher’s skills and competence and the learners’ readiness, strength, and intelligence. Also, there is no doubt that motivation has a great impact on the success of the language learning and acquisition process. Therefore, the research in the field of teaching foreign languages should be concerned with studying the cognitive, affective, cultural, and social variables, rather than attributing failure to innate aspects. The research benefits program developers in building curricula, teachers in preparing their lessons and educational plans, and curriculum developers as well.